Card clothing with misaligned teeth for the card: Carding mechanism and application. Issue 1 (January 2023) - He, Shanshan; Cheng, Longdi; Xue, Wenliang; Lu, Zhong; Chen, Liguo; Shao, Ruiqi
In the carding region between flats and the cylinder, carding efficiency is limited because small tufts are prone to move or are embedded in channels between two lines of teeth. In our previous research, simulation on airflow and fiber deformation in this area has been discussed. It turns out that when teeth are misaligned alternatively lengthwise, fibers have larger swing scopes and are more easily caught by adjacent teeth. In this project, further research has been done on this card clothing with misaligned teeth (M-CC) and compared with card clothing with traditional teeth. Simulations by the discrete phase model have been applied to investigate the effect of teeth arrangement on contacting chances of fibers and teeth, which shows an increase of 1.3 times. Besides, the teeth's ability of fiber grasping and transferring has been analyzed and they are shown to be enhanced by misalignment. To realize the processing requirement on the teeth shape of M-CC, a specialized teeth reshaping device has also been designed here. Contrast experiments have been done to look into the fiber quality in slivers and yarn quality. With the application of M-CC, the neps and short fiber content (both short fiber content by weight and short fiber content by number) in slivers declined by 4.08%, 25.42% and 33.92%, respectively. In addition, when mounted on a card machine, records of energy and weight on 30 cotton laps manifested in intensive carding forces and advanced fiber utilization. Yarn from the M-CC group also has better performance in evenness (2.87%) and no significant changes in tenacity properties.